Acute respiratory distress syndrome in the forward environment. Retrospective analysis of acute respiratory distress syndrome cases among French Army war casualties. Issue 2 (August 2020) - Schmitt, Johan; Boutonnet, Mathieu; Goutorbe, Philippe; Raynaud, Laurent; Carfantan, Cyril; Luft, Antoine; Pasquier, Pierre; Meaudre, Eric; Bordes, Julien
Abstract : BACKGROUND: According to the Joint Theater Trauma Registry, 26% to 33% of war casualties develop acute respiratory distress syndrome (ARDS), with high mortality. Here, we aimed to describe ARDS incidence and severity among patients evacuated from war zones and admitted to French intensive care units (ICUs). METHODS: We performed an observational retrospective multicentric review of all patients evacuated from war zones and admitted to French ICUs between 2003 and 2018. Our analysis included all medical and trauma patients developing ARDS according to the Berlin definition. We evaluated ARDS incidence, and determined ARDS severity from arterial blood gas analysis. Analyzed parameters included invasive ventilation duration, ARDS treatments, ICU stay length, and 30-day and 90-day mortalities. RESULTS: Among 141 included patients (84% military; median age, 30 years), 57 (42%) developed ARDS. Acute respiratory distress syndrome was mild in 13 (22%) patients, moderate in 24 (42%) patients, and severe in 20 (36%) patients. Evacuation occurred in less than 26 hours for 32 war casualties, 17 non–war-related trauma patients, and 8 medical patients. Among severe trauma patients, median Injury Severity Score was 34, and Abbreviated Injury Scale thorax was 3. Upon French ICU admission, median partial pressure of oxygen in arterial blood/inspirated fraction of oxygen ratio was 241 [144–296]. Administered ARDS treatments included intubation (98%, n = 56), protective ventilation (87%, n = 49), neuromuscular blockade (76%, n = 43), prone position (16%, n = 9), inhaled nitric oxide (10%, n = 6), almitrine (7%, n = 7), and extracorporeal life support (4%, n = 2). Median duration of invasive ventilation was 13 days, ICU stay was 18 days, 30-day mortality was 14%, and 90-day mortality was 21%. CONCLUSION: Acute respiratory distress syndrome was frequent and severe among French patients evacuated from war theaters. Improved treatment capacities are needed in the forward environment—for example, a specialized US team can provide extracorporeal life support for highly hypoxemic war casualties. LEVEL OF EVIDENCE: Prognostic and epidemiological study, level III.